Cognitive and Behavioral Abnormalities of Pediatric Diseases 2010
DOI: 10.1093/oso/9780195342680.003.0063
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral and Cognitive Manifestations of Blindness in Children

Abstract: Ground-breaking progress in the field of neurodevelopmental disorders has allowed us far more insight into blindness and visual impairment (VI). The field of cognitive neuroscience has now established itself solidly in the literature, combining the knowledge from cognitive psychology, clinical studies related to brain damage, and neuroscience to open the way to significant advances in understanding. In recent years, the optimism engendered from the adult studies has played a large part in providing the impetus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Further, childhood blindness requires resources from and collaboration between medical, community, and educational services to nurture the growing child. Providing sight to a child who may otherwise go blind is thus more than just about restoring vision [2].…”
Section: Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, childhood blindness requires resources from and collaboration between medical, community, and educational services to nurture the growing child. Providing sight to a child who may otherwise go blind is thus more than just about restoring vision [2].…”
Section: Opinionmentioning
confidence: 99%
“…While studies have not shown any significant IQ differences in blind children compared to their seeing counterparts, they have indicated that children with congenital visual impairment have discrepancies in language presentation. Though they may develop normal grammar, vocabulary, and other components that allow a person to communicate, their pragmatic language skills may be hindered, as these develop with visual cues from interactions in various social contexts [2].…”
Section: Opinionmentioning
confidence: 99%
“…Lack of visual cues may lead to greater inactivity (Martinsen, 1994; Pérez-Pereira and Conti-Ramsden, 1999) and, in many settings, children with blindness are described as passive (Dale and Salt, 2007; Martinsen, 1994; Pérez-Pereira and Conti-Ramsden, 1999; Sandler, 1963; Sandler and Hobson, 2001). Signals of attention, interest and activity in children with congenital blindness may also be idiosyncratic and difficult to recognize (Fraiberg, 1977; Martinsen, 1994; Pérez-Pereira and Conti-Ramsden, 1999; Pring and Tadic, 2010). Many individuals with congenital blindness have other co-morbid disorders, like intellectual disability and autism spectrum disorders (ASDs) (Mukaddes et al, 2007; Sonksen and Dale, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Children with congenital blindness comprise a heterogeneous group of individuals with differences in general cognitive level, activity, mobility skills, communication and social and linguistic skills, amongst others things (Fraiberg, 1977; Gense and Gense, 2005, Pring and Tadic, 2010; Warren,1994). As a result of their loss of sight and the inhibitions this has on the children’s physical activity, the children are to a great degree dependent on their caregivers to organise the environment and structure their interaction to promote meaningful activity (Erin, 2000; Fraiberg, 1977; Gense and Gense, 2005; Howley and Preece, 2003; Jordan, 2005; Von Tetzchner and Martinsen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To succeed in getting children with autism and blindness to participate in activities, it is important to assess what may be of interest to each individual (Bruce and Vargas, 2007; Gense and Gense, 2005). A complicating feature in this respect is that the child’s behaviour is often less legible than that of a sighted child (Fraiberg, 1977; Martinsen, 1994; Pérez-Pereira and Conti-Ramsden, 1999, 2005; Pring and Tadic, 2010), and the children often show their interest in ways other than sighted children (Erin, 2000; Gense and Gense, 2005), which in turn makes it more difficult to understand the children. It can result in the environment getting fewer cues to react and respond to the child’s behaviour and initiatives (Fraiberg, 1977; Martinsen, 1994; Pérez-Pereira and Conti-Ramsden, 2005; Rogers and Puchalski, 1984; Warren, 1994).…”
Section: Introductionmentioning
confidence: 99%